2014
DOI: 10.1177/8755122514552497
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Time in Therapeutic Range on Warfarin Therapy Between Face-to-Face and Telephone Follow-Up in a VA Medical Center

Abstract: Background: Few studies have evaluated percent time in therapeutic range (TTR) for warfarin managed via face-to-face (FF) to telephone (TELE) visits-all finding no difference between groups. Objective: Compare and evaluate TTR for warfarin in patients who received pharmacist-managed care via FF or TELE. Methods: Single-center, retrospective study. Eligible participants were ≥18 years old, on indefinite warfarin therapy, followed by clinical pharmacists via FF or TELE from 2010 to 2012. Primary outcome (TTR) ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 18 publications
(20 reference statements)
3
30
2
Order By: Relevance
“…However, the incidence of minor bleeding events was higher in the Alfalfa app group. This finding was similar to the results reported by Blissit et al, who concluded that the incidence of minor bleeding events was higher in the online anticoagulation management group [ 30 ]. The top three minor bleeding types in the offline group were nose bleeding (7 cases), gum bleeding (7 cases), and hematuria (4 cases).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the incidence of minor bleeding events was higher in the Alfalfa app group. This finding was similar to the results reported by Blissit et al, who concluded that the incidence of minor bleeding events was higher in the online anticoagulation management group [ 30 ]. The top three minor bleeding types in the offline group were nose bleeding (7 cases), gum bleeding (7 cases), and hematuria (4 cases).…”
Section: Discussionsupporting
confidence: 92%
“…The studies by Xia et al and Cryder et al showed that there were fewer anticoagulation-related hospital admissions in the online anticoagulation group [4,27]. Most studies have reported that there are no differences in the incidence of major bleeding events between the two groups [5,[27][28][29][30][31][32]. Our findings revealed that the incidences of thromboembolic events were similar between the two groups.…”
Section: Discussionsupporting
confidence: 64%
“…With warfarin, the disadvantages are as follows: wide array of pharmacokinetic variability, the multiple drug-drug interactions, and the need for restrictions on diet and alcohol consumption, and consequently the need for frequent blood monitoring of INR, a normalized ratio of prothrombin time, which measures the narrow therapeutic window of warfarin's efficacy. It has been found that warfarin stays within the therapeutic range rarely above 65% of the duration of the therapy [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The sample size ranged from 1 [74] to 217,014 [62], with a median of 157 and a mean of 7977 participants per study. Overall, 21 studies enrolled ≥100 participants [51,[53][54][55][56][57][58][59][60]62,63,[65][66][67][68][69][70]72,73,76,80] and 11 had <100 participants [42,52,61,64,71,74,75,[77][78][79]81].…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
“…Of the 32 included studies, 12 (34%) studied malignant hematological conditions [42,53,[58][59][60][61]64,67,69,77,80,81], 18 (59%) studied nonmalignant conditions with percentages [51,52,[54][55][56][57]62,63,65,66,68,[70][71][72][73][74]76,78], and 2 (6%) studied both malignant and nonmalignant conditions [75,79]. [68,79], 1 (3%) was a case study [74], 1 (3%) was a pre-post study [54], 1 (3%) was a noncomparative prospective study [59], and 1 (3%) was a prospective cohort study [66].…”
Section: Description Of the Included Studiesmentioning
confidence: 99%